Rosiglitazone activation of PPARγ suppresses fractalkine signaling - Wan, Yihong (Society for Endocrinology, 2010)
The nuclear receptor peroxisome proliferator-activated receptor γ (PPARγ) is a key transcriptional regulator of both lipid metabolism and inflammation. The importance of PPARγ is accentuated by the widespread use of synthetic PPARγ agonists, thiazolidinediones (such as rosiglitazone), as drugs for insulin resistance and type II diabetes. Fractalkine (FKN) and FKN receptor (FR) play an important role in the immune responses by regulating leukocyte migration and adhesion to inflamed peripheral tissues. In this study, we have identified a novel link between PPARγ activation and FKN signaling. On one hand, the activation of PPARγ by rosiglitazone in macrophages not only represses the transcription of the FR gene, but also prevents the plasma membrane translocation of the FR protein. On the other hand, the activation of PPARγ by rosiglitazone in endothelial cells also impedes the nuclear export of FKN. Together, these data suggest that PPARγ activation represses FKN signaling. These findings indicate a previously unrecognized mechanism that may contribute to the anti-inflammatory effect of PPARγ.